TRPC3 contributes to regulation of cardiac contractility and arrhythmogenesis by dynamic interaction with NCX1. (28th January 2015) - Doleschal, Bernhard; Primessnig, Uwe; Wölkart, Gerald; Wolf, Stefan; Schernthaner, Michaela; Lichtenegger, Michaela; Glasnov, Toma N.; Kappe, C. Oliver; Mayer, Bernd; Antoons, Gudrun; Heinzel, Frank; Poteser, Michael; et al.
Abstract: Aim: TRPC3 is a non-selective cation channel, which forms a Ca 2+ entry pathway involved in cardiac remodelling. Our aim was to analyse acute electrophysiological and contractile consequences of TRPC3 activation in the heart. Methods and results: We used a murine model of cardiac TRPC3 overexpression and a novel TRPC3 agonist, GSK1702934A, to uncover (patho)physiological functions of TRPC3. GSK1702934A induced a transient, non-selective conductance and prolonged action potentials in TRPC3-overexpressing myocytes but lacked significant electrophysiological effects in wild-type myocytes. GSK1702934A transiently enhanced contractility and evoked arrhythmias in isolated Langendorff hearts from TRPC3-overexpressing but not wild-type mice. Interestingly, pro-arrhythmic effects outlasted TRPC3 current activation, were prevented by enhanced intracellular Ca 2+ buffering, and suppressed by the NCX inhibitor 3′, 4′-dichlorobenzamil hydrochloride. GSK1702934A substantially promoted NCX currents in TRPC3-overexpressing myocytes. The TRPC3-dependent electrophysiologic, pro-arrhythmic, and inotropic actions of GSK1702934A were mimicked by angiotensin II (AngII). Immunocytochemistry demonstrated colocalization of TRPC3 with NCX1 and disruption of local interaction upon channel activation by either GSK1702934A or AngII. Conclusion: Cardiac TRPC3 mediates Ca 2+ and Na + entry in proximity of NCX1, thereby elevating cellular Ca 2+ levels and contractility. Excessive activation of TRPC3 is associated with transient cellular Ca 2+ overload, spatial uncoupling between TRPC3 and NCX1, and arrhythmogenesis. We propose TRPC3-NCX micro/nanodomain communication as determinant of cardiac contractility and susceptibility to arrhythmogenic stimuli.